A scale to measure the attitude towards improved fish processing methods - Kandoran, M.K., Thiagarajan, R. Mohan, B. and (Fishery Technology, 2021)
An attitude scale was constructed to measure the attitude of fisherwomen towards improved fish processing methods. To construct the attitude scale, ’scale’ and â€˜Qâ€™ values (the interquartile ranges) were calculated for 31 statements selected, based on the opinion of 34 judges. Based on the ’scale’ and â€˜Qâ€™ values 16 statements were selected with eight favorable statements and eight unfavorable statements. The weightages given were 3, 2 and 1 for favorable statements and 1, 2 and 3 for unfavorable statements.